1996
DOI: 10.1111/j.1476-5381.1996.tb15681.x
|View full text |Cite
|
Sign up to set email alerts
|

Adrenoceptor‐ and cholinoceptor‐mediated mechanisms in the regulation of 5‐hydroxytryptamine release from isolated tracheae of newborn rabbits

Abstract: 1 Isolated tracheae of newborn rabbits were incubated in vitro and the outflow of 5-hydroxytryptamine (5-HT) was determined by h.p.l.c. with electrochemical detection. Evidence has previously been provided that this 5-HT outflow derives from neuroendocrine epithelial (NEE) cells of the airway mucosa. 4 5-HT outflow evoked by 10 IM phenylephrine was inhibited by 65% in the presence of 1 gM forskolin and abolished in the presence of 10 gM forskolin. 5 5-HT outflow evoked by 10 gM phenylephrine was inhibited by a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
1
0

Year Published

1997
1997
2010
2010

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 12 publications
(2 citation statements)
references
References 43 publications
1
1
0
Order By: Relevance
“…Interestingly, we found that the nicotinic receptor was colocalized in the same cells in which 5-HT was observed, which is in agreement with a published study performed in hamster lungs [38]. Other research groups have already reported that stimulation of the nicotinic receptor by nicotine induces the release of 5-HT from PNECs [30,39]. In our study, PNECs might be a potential source of 5-HT, at least in sensitized guinea-pigs, from which 5-HT release may be triggered by ACh during a dose-response curve.…”
Section: Discussionsupporting
confidence: 93%
“…Interestingly, we found that the nicotinic receptor was colocalized in the same cells in which 5-HT was observed, which is in agreement with a published study performed in hamster lungs [38]. Other research groups have already reported that stimulation of the nicotinic receptor by nicotine induces the release of 5-HT from PNECs [30,39]. In our study, PNECs might be a potential source of 5-HT, at least in sensitized guinea-pigs, from which 5-HT release may be triggered by ACh during a dose-response curve.…”
Section: Discussionsupporting
confidence: 93%
“…The existence of various cell surface receptors in the upper airway that modulate levels of intracellular second messengers is well characterized. The co-administration of various catecholamines of adrenergic receptor agonists, that act through elevating intracellular cAMP levels, can potentially enhance the absorption of inhaled nucleoside analogues (Freitag et al, 1996). On the other hand, the presence of muscarinic, cholinergic receptor antagonists, that prevents the elevation of [Ca 2+ ] i , can add up to the same outcome if included in similar pulmonary formulations of nucleoside drugs (Reinheimer et al, 2000).…”
Section: Modulation Of Nucleoside Exit Across Basolateral Membrane Ofmentioning
confidence: 98%